2010
DOI: 10.2139/ssrn.1672522
|View full text |Cite
|
Sign up to set email alerts
|

Borobudur Was Built Algorithmically

Abstract: The self-similarity of Indonesian Borobudur Temple is observed through the dimensionality of stupa that is hypothetically closely related to whole architectural body. Fractal dimension is calculated by using the cube counting method and found that the dimension is 2.325, which is laid between the two-dimensional plane and three dimensional space. The applied fractal geometry and self-similarity of the building is emerged as the building process implement the metric rules, since there is no universal metric sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
6
0
3
Order By: Relevance
“…Sehingga diperoleh dimensi Candi Borobudur, yaitu (D) = 2,3252. Berdasarkan hasil perhitungan tersebut, 2<D<3, sehingga struktur bangunan Candi Borobudur bukan bangun ruang 3 dimensi maupun 2 dimensi, melainkan Candi Borobudur berada diantara dimensi 2 dan 3 (Situngkir, 2010).…”
Section: Hasil Dan Pembahasanunclassified
See 2 more Smart Citations
“…Sehingga diperoleh dimensi Candi Borobudur, yaitu (D) = 2,3252. Berdasarkan hasil perhitungan tersebut, 2<D<3, sehingga struktur bangunan Candi Borobudur bukan bangun ruang 3 dimensi maupun 2 dimensi, melainkan Candi Borobudur berada diantara dimensi 2 dan 3 (Situngkir, 2010).…”
Section: Hasil Dan Pembahasanunclassified
“…Gambar 8. Konsep bangun ruang pada Candi Borobudur jika dilihat dari atas dan samping (Situngkir, 2010) Konsep matematika mengenai perbandingan dengan pola teratur juga terdapat pada Candi Borobudur. Hal ini terlihat dari jumlah stupa pada tingkat Arupadhatu, yaitu pada lantai 7 berjumlah 16 stupa, lantai 8 berjumlah 24 stupa, dan lantai 9 berjumlah 32 stupa (Larisa, 2011, p.20).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Research by Situngkir (2010) found that Candi (temple) Borobudur was built algorithmically from which it applied fractal geometry and self-similarity. The essential building of Borobudur is a stupa, but not with a commonly stupa-shaped dome, instead it is a punden (holy place) with six levels of a square (Soetarno, 1988, p. 90).…”
Section: Characteristic Of Mathematics At Borobudur Temple Buildingmentioning
confidence: 99%
“…King Smaratungga built this enormous temple between 780 and 830 BC [1]. The study of this temple by Situngkir proved that the building of Borobudur temple was arranged in a symmetrical form and obeyed geometric laws [2]. When viewed from above, a symmetrical pattern formed from the large building which explains the philosophical concepts of Buddhist teachings.…”
Section: Introductionmentioning
confidence: 99%